Smash, crash, topple, roll! : the inventive Rube Goldberg : a life in comics, contraptions, and six simple machines - Thimmesh, Catherine (Chronicle Books, 2025)
"A joyfully illustrated picture book biography of Rube Goldberg for STEM-loving children and the many people who enjoy doing simple tasks the hard way - plus an introduction to the six simple machines. Award-winning author Catherine Thimmesh and artist Shanda McCloskey introduce readers to Rube Goldberg's life and creative legacy, and put the tools for making real-life Rube Goldberg machines in their hands. Part biography, part inspiration, and part physics how-to, this book will light a fire in budding inventors, artists, and thinkers of all ages"--